Healthcare Professionals Delivering Quality and Appropriate Services to Patients With HIV - A Elfaki, Badria (Nursing and Health Sciences Journal (NHSJ), 2024)
Healthcare professionals (HCP) strive to deliver appropriate Human Immunodeficiency Virus (HIV) care practices that can enhance patient outcomes and quality practice. We conducted a comprehensive analysis of healthcare professionals' HIV care best practices published between 2012 and 2022. The review includes HPC practices that successfully reached the intended results depending on their objectives. Two themes emerged from the eight publications reviewed: (a) the significance of linking HCP services to newly diagnosed HIV-positive individuals and (b) the relevance of integrated and comprehensive service provision in enhancing patient outcomes. This review was hindered by inconsistent reporting and arbitrary usage of "Appropriate HIV care practices."